"Readiness for enhanced healthy aging" nursing diagnosis: Content validation by experts. Issue 1 (20th February 2022) - Cardoso, Rosane Barreto; Caldas, Célia Pereira; Brandão, Marcos Antônio Gomes; de Souza, Priscilla Alfradique; Santana, Rosimere Ferreira
Abstract: Purpose: To validate the content nursing diagnosis "Readiness for enhanced healthy aging." Methods: Descriptive, methodological study of diagnostic content validation, using the Fehring model. The sample consisted of 74 nurses experts in gerontology, with knowledge in NANDA‐I nursing diagnoses. Findings: The title, one definition, and the three defining characteristics proposed for the diagnosis were validated, as well as the suggestion of domain and location class in NANDA‐I Taxonomy II. The Diagnostic Content Validity Index was 0.81. Conclusions: The validation of the diagnostic content by experts was fundamental for adequacy of the elements of the proposed diagnosis, which supported the elaboration of the diagnostic framework for submission to the NANDA‐I taxonomy. Implication for nursing practice: The diagnosis "Readiness for enhanced healthy aging" can help nurses understand the phenomenon of "Healthy Aging" and, consequently, will support the planning and implementation of interventions aimed at promoting the health of the elderly population and those in the aging process. In addition, this diagnosis will offer nurses the opportunity to rethink health promotion strategies in their care plan, making a commitment to the population regarding the promotion of healthy aging, as recommended by the Word Health Organization.